Long‐term follow‐up of the thyroid gland after treatment with 131I‐Metaiodobenzylguanidine in children with neuroblastoma: Importance of continuous surveillance. Issue 11 (6th July 2013) - Clement, S.C.; van Eck‐Smit, B.L.F.; van Trotsenburg, A.S.P.; Kremer, L.C.M.; Tytgat, G.A.M.; van Santen, H.M.
Abstract Background Thyroid dysfunction has been reported in up to 52% of patients 1.4 years after treatment with 131I‐Metaiodobenzylguanidine (MIBG) in children with neuroblastoma (NBL), despite the use of potassium‐iodide (KI). Our aim was to investigate if the incidence and severity of thyroid damage increases in time. Materials and Methods All long‐term survivors of childhood NBL treated with 131I‐MIBG in the period 1989–1999 in our center (n = 16 of 43) were evaluated. During exposure to 131I‐MIBG, patients received 100 mg KI per day as thyroid protection. All MIBG images were evaluated for thyroid uptake of radio‐iodine. Thyroid dysfunction was defined as a plasma thyrotropin concentration above the institutional age‐related reference ranges (thyrotropin elevation, TE) or using thyroxine at last moment of follow‐up. In all, ultrasound investigation of the thyroid was performed. Results Fifteen years after treatment with 131I‐MIBG, in 81% (n = 13) thyroid disorders were diagnosed. Eight survivors (50%) were treated with thyroxine. Thyroid nodules were found in nine survivors, of which two were diagnosed with papillary thyroid carcinoma. In 28% of 131I‐MIBG‐images radio‐iodine uptake in the thyroid gland was seen, but no correlation was found between thyroidal radio‐iodine uptake and thyroid disorders. Conclusions Despite protection with KI during exposure to 131I‐MIBG in childhood, the occurrence of thyroid disorders is high and increases in time. Continuous screening for thyroid dysfunction and nodules in these survivors is recommended. Other ways to protect the thyroid gland should be further evaluated. Pediatr Blood Cancer 2013;60:1833–1838. © 2013 Wiley Periodicals, Inc.